Production of seven cucumber (Cucumis sativus L.) genotypes grown under greenhouse conditions - Cruz-Coronado, José Aníbal (2020)
The objective of the study was to evaluate yield and quality of seven medium fruit size parthenocarpic cucumber genotypes (Corinto, Katrina, Macario, Modan, Paraíso, Primavera and 22-20-782) grown under greenhouse conditions at the Agricultural Experimental Station Fabio Baudrit Moreno, located in Alajuela, Costa Rica. The crop was planted on coconut fiber as substrate, pruned to one stem per plant and managed with fertigation.  Data show a wide variability among genotypes with respect to days to start of flowering (17 - 20 days after transplant –d.a.t.-), days to start of harvest (28 - 30 d.a.t.), fruit length (16,56 - 21,30 cm), fruit diameter (42,94 - 54,09 mm), total number of fruits per plant (26,31 - 49,41), fruit weight (215,41 - 269,89 g), commercial yield (13,66 - 22,66 kg/m2), total yield (18,11 - 28,41 kg/m2), and percentage of total soluble solids (2,89 - 3,22 °Brix). In general, first quality cucumber fruits showed higher length, diameter and percentage of total soluble solids than second quality and waste quality fruits.  22-20-782 and Katrina genotypes produced the highest commercial (20,89 and 22,66 kg/m2, respectively) and first quality yield (12,48 and 12,49 kg/m2, respectively), so they were the best adapted to the conditions of the trial; however, their fruits were smaller (lower length, diameter and weight) compared to the other genotypes, which could affect their commercial potential in Costa Rica.